ANALYSIS OF GEOMETRY DEVELOPMENT OF AIRSIDE FACILITIES AT FATMAWATI SOEKARNO AIRPORT BENGKULU PROVINCE USING A SIMULATION APPROACH - Septia Rahayu, Anis
Aircraft movements increase every year in line with the increase in passenger growth. However, since the Covid-19 pandemic hit the world, it has had an extraordinary impact, including decreased aircraft movements. Fatmawati Soekarno Airport, Bengkulu Province, is one of the airports affected by the Covid-19 pandemic. Based on passenger data at Fatmawati Soekarno Airport, the number of passengers (demand) in 2010 - 2018 continued to increase, but in 2019 - 2021 the number of passengers decreased. So that this study aims to review the development stages of Fatmawati Soekarno Airport based on projected passenger movements and consider the influence of the Covid-19 pandemic. The analysis of the development of Fatmawati Soekarno Airport, Bengkulu Province, is planned for a period of 20 years, 2022-2041. The existing airside facilities at the airport were evaluated, then a development analysis was carried out using the help of Simmod software to produce ground delay time, departure queue time, and runway occupancy time values as performance indicators. After evaluation and analysis, it then selects geometry development alternatives with and/or without the addition of airside facility components based on airside facility performance indicators that produce tolerable delay rate values under FAA regulations. Based on the results of the analysis, it was found that the peak hour capacity at Fatmawati Soekarno Airport was 48 operations/hour with an annual service volume (ASV) of 67,680 operations/year. The results of the evaluation of the existing airside facility phase 1 in 2025, in the form of an extension to 2,600 m and phase 2 in 2038, were arranged to configure the aircraft stand on the apron to nose in with 11 aircraft stands with apron dimensions of 475 x 80 m. The results of the development stage analysis obtained in phase 1 of 2024 are existing conditions, and phase 2 of development in 2038 in the form of the addition of a parallel taxiway.